On the Issue of Legal Regulations of Criminal Responsibility for Pedophilia - A. V. Kuznetsov; Y. V. Dracheva; V. N. Krailo (Сибирское юридическое обозрение, 2013)
In this article the authors focus on the issues of criminal law regulation responsibility for crimes against sexual integrity of minors. Here are submitted for consideration the problematic crimes qualification issues and offered the ways of their solution by the enforcer before making the appropriate alterations in the criminal legislation, or official clarification of the Plenum of the RF Supreme Court.